L’IMPACT DU SOUTIEN SOCIAL SUR LE SUJET MALADE DU CANCER ET SUR SON PARCOURS DE MALADIE ETUDE QUALITATIVE - Laura Petrescu Perlier (European Scientific Journal, ESJ, 2014)
Although proved as an important ingredient to physical and mental health, social support is a critical and yet underutilized resource when undergoing cancer care. My first objective is to provide deeper comprehension of the perceived social support and its relationship with patients’ representations of cancer. Therefore, my study goes towards a greater acceptance of care and better wellbeing of cancer patients. The present article represents part of an extended research, dealing with relations between social support, social norm and patients’ representations. Unconscious aspects of cancer management, hidden behind defence mechanisms of patients confronted to cancer disclosure, can block or hinder their demand for support. First results on a major theme of my research are hereby revealed: the influence of the social support on patient’s life, relationships, opinions and health behaviour. This main theme gives expression to collective voices across participants. This qualitative study is characterised by respect of subjective meaning and perception of cancer and social support by the patient, even if this meaning is opposite to common representations. Whatever be the form of social support (emotional, appraisal, informational or instrumental support) patients need it, even if they are reluctant to ask for help. That’s why most of the time social support it is not explicitly expressed. Patients need to know that “somebody is there for them”, want to be considered as an “entire person” and to be free in choosing social support upon their own criteria and at the right time for them. Offering social support seems to be as important for some patients as receiving it.